The rabbinic conversion of Judaism : the unique perspective of the Bavli on conversion and the construction of Jewish identity - Lavie-Levkovitch, Moshe. (Ancient Judaism and Early Christianity, 2017)
In this volume, Moshe Lavee offers an account of crucial internal developments in the rabbinic corpus, and shows how the Babylonian Talmud dramatically challenged and extended the rabbinic model of conversion to Judaism. The history of conversion to Judaism has long fascinated Jews along a broad ideological continuum. This book demonstrates the rabbis in Babylonia further reworked former traditions about conversion in ever more stringent direction, shifting the focus of identity demarcation towards genealogy and bodily perspectives. By applying a reading-strategy that emphasizes late Babylonian literary developments, Lavee sheds critical light on a broader discourse regarding the nature and boundaries of Jewish identity.